PENGEMBANGAN PRODUK BERBASIS ARSITEKTUR MODULAR - Rahayu, Siti (Journal of Management and Business, 2003)
The intensive market competition requires company to quickly respond every single change that happen in order to offer a - state of the art - product to customer. These fact strive company accommodating all the inputs from various sources with different perspective. Therefore, it is necessary for a company to create a team that involve various management functions.These various function are organised in the form of modular architecture which consist of product architecture, process, and knowledge. A proper comprehension in product structure, production process, and knowledge in market technology should make company more rapidly in promoting their product in efficiently lower cost.